A multifactorial, criteria-based progressive algorithm for hamstring injury treatment - Mendiguchia, J.; Martinez-Ruiz, E.; Eduard, P.; Morin, J.-B.; Martinez-Martinez, F.; Idoate, F.; Mendez-Villanueva, A. (Medicine & Science in Sports & Exercise, 2018)
Introduction Given the prevalence of hamstring injuries in football, a rehabilitation program that effectively promotes muscle tissue repair and functional recovery is paramount to minimize reinjury risk and optimize player performance and availability.